Telepractice Reading Intervention using Orton-Gillingham Approach for Child with Dyslexia - Puti Aulia Rahma; Lia Mawarsari Boediman (Psikostudia : Jurnal Psikologi, 2023)
Specific learning disorders are one of the neurodevelopmental disorders that cause obstacles in a person's academic performance. One category of specific learning disorders is dyslexia, which is a learning disorder caused by reading difficulties. Dyslexia can have a negative impact on children's well-being and learning motivation, therefore special interventions need to be carried out to improve reading skills. One of the most widely used interventions in the world is the reading intervention with the Orton-Gillingham approach. Current technological developments allow practitioners to conduct telepractice, or the implementation of assessments and therapies through online means. Telepractice is gaining popularity because with this method, practitioners can reach groups in need even though they are far apart. This study aimed to see if reading interventions with the Orton-Gillingham approach given through telepractice could improve beginning reading skills. The study participants were 10-year-old boys who had mild dyslexia. This study consisted of 10 sessions divided into pre-test, 8 intervention sessions, and post-test. Early Grade Reading Assessment (EGRA) was used to measure participants' reading ability before and after the intervention. The results showed an increase in participants' EGRA scores after the intervention was given. In conclusion, interventions with the Orton-Gillingham approach can be provided using telepractice methods and are useful in improving the early reading skills of children with mild dyslexia.Gangguan belajar spesifik merupakan salah satu gangguan neurodevelopmental yang menyebabkan hambatan dalam performa akademik seseorang. Salah satu kategori dari gangguan belajar spesifik adalah disleksia, yaitu gangguan belajar yang disebabkan oleh kesulitan membaca. Disleksia dapat menimbulkan dampak negative terhadap kesejahteraan dan motivasi belajar anak, oleh karena itu perlu dilakukan intervensi khusus untuk meningkatkan kemampuan membaca. Salah satu intervensi yang paling banyak digunakan di dunia adalah intervensi membaca dengan pendekatan Orton-Gillingham. Perkembangan teknologi saat ini memungkinkan praktisi untuk melakukan telepraktik, atau pelaksanaan asesmen dan terapi melalui sarana daring. Telepraktik mulai populer karena dengan metode ini, praktisi dapat menjangkau kelompok yang membutuhkan meskipun terpisah jarak yang jauh. Penelitian ini bertujuan untuk melihat apakah intervensi membaca dengan pendekatan Orton-Gillingham yang diberikan melalui telepraktik dapat meningkatkan kemampuan membaca permulaan. Partisipan penelitian adalah anak laki-laki berusia 10 tahun yang memiliki disleksia taraf ringan. Penelitian ini terdiri dari 10 sesi yang terbagi menjadi pre-tes, 8 sesi intervensi, dan post-tes. Early Grade Reading Assessment (EGRA) digunakan untuk mengukur kemampuan membaca partisipan sebelum dan sesudah intervensi. Hasil penelitian menunjukkan adanya peningkatan pada skor EGRA partisipan setelah intervensi diberikan. Sebagai kesimpulan, intervensi dengan pendekatan Orton-Gillingham dapat diberikan menggunakan metode telepraktik serta bermanfaat dalam meningkatkan kemampuan membaca permulaan anak dengan disleksia taraf ringan.